Elementary Geometry for College Students (6th Edition)

Published by Brooks Cole
ISBN 10:
ISBN 13:

Chapter 1 - Section 1.5 - Introduction to Geometric Proof - Exercises - Page 44: 38

Answer

a=b a-c=b-c c=d a-c=b-d

Work Step by Step

a=b is given in the question. Because a=b then if the same amount (c) is taken from both a and b, the two sides will still be equal. Therefore a-c=b-c. c=d is given in the question. If c=d then d can replace c in any equation, therefore b-c=b-d. We already know that a-c=b-c, therefore a-c=b-d as well. Therefore a-c=b-d is proved.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.